Modelagem plana do vestuário: aplicação e experiências de design participativo - SANTIAGO, Élida Belquice de Araújo (2020)
Modeling is one of the main steps in the process of developing a clothing product, to master the technique requires a series of skills and competences that are acquired during the exercise and learning process. Assuming gaps in current methodologies for the development of flat clothing modeling, it is presented through a methodological proposal based on participatory molds, an analysis of experiences, systematization and articulation of tools, methods and technicians in a participatory process with documents. This research as to the purposes is descriptive, and has as a methodological procedure of research-action, based on definitions from principles and participatory actions. As a bibliographic research instrument, a systematic and unsystematic literature review was carried out in order to compose theoretical substrate for a research, as well as to identify gaps and tensions on the axes: design, participatory design and flat clothing modeling. The theoretical chapter reflects on the practice of participatory design in convergence with methodological approaches and foundations for its application in the problematics of the teaching field. With the surveys, there is a great lack of studies in the area as well as a fertile field for research production. As results, we present recommendations for flat modeling, through a didactic proposal for the execution of contents and activities to competences in the teaching of the discipline, assembled from the application of participatory design tools with a group of professors from the Federal Institute of Piauí. A participatory methodological model for solutions is also proposed, with a description of the entire process used in this research, as well as the tools used and applied in the shared experiences.